PENERAPAN METODE SUPPORT VECTOR MACHINE (SVM) UNTUK KLASIFIKASI UANG KULIAH TUNGGAL DI UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Nur Leli; Fibri Rakhmawati; Rina Widyasari (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
North Sumatra State Islamic University is one of the State Universities in North Sumatra Medan which has implemented Single Tuition Fee (UKT). UKT is the name of a payment system that is currently in effect throughout the State Islamic Religious Colleges (PTKIN). In the UKT process, there are still problems, there are students at the State Islamic University of North Sumatra whose parents' economy is classified as low but gets a high UKT group, while their parents' economy is high but gets a low UKT group. The variables used are father's education, mother's education, father's income, mother's income and number of parents' dependents. The UKT groups are UKT 1, UKT 2, UKT 3, UKT 4, UKT 5, UKT 6 and UKT 7. The accuracy of the performance vector from the classification of the support vector machine method using cross validation is 61.33%